Correlation between hemoglobin and hematocrit levels of women in the third trimester of pregnancy and those of their newborns in Cusco, Peru - Frisancho Angulo, Vanessa (2025)
Objective: To determine the correlation between hemoglobin (Hb) and hematocrit (Hct) levels of women in the third trimester of pregnancy and Hb and Hct levels of their newborns at EsSalud Cusco. Materials and methods: A cross-sectional observational study conducted in mothers and their newborns at EsSalud Cusco. The study included pregnant women in the third trimester of pregnancy with no history of anemia and who had attended at least six prenatal visits, as well as full-term newborns without marked fluctuations in birth weight. The sample comprised 484 individuals (242 mother-newborn dyads). Data were analyzed using IBM SPSS Statistics and JASP, applying correlation tests and multivariate analyses. Results: The analysis included 242 mother-newborn dyads. Study variables consisted of maternal age (median: 30 years), gestational age (40 weeks), number of prenatal visits (8) and neonatal measurements (mean birth weight: 3286.446 g and mean length: 49.031 cm). Shapiro-Wilk tests indicated non normality for variables such as gestational age and birth length, suggesting the need for nonparametric tests. No statistically significant correlations were observed between maternal and neonatal Hb and Hct levels. However, strong correlations were found between maternal (ρ = 0.935) and neonatal (ρ = 0.999) Hb and Hct levels. Gestational age was correlated with birth weight (ρ = 0.326) and length (ρ = 0.298). No significant differences in Hb and Hct levels were found between genders. Conclusions: Variables such as gestational age and number of prenatal visits showed stable and homogeneous distributions. The lack of significant correlations between certain maternal and neonatal hematologic parameters suggests that these factors may function independently in the transmission of hematological characteristics at high altitude. However, the strong correlations observed support the internal consistency of the measurements and highlight the influence of gestational age on neonatal development. The absence of statistically significant correlations between maternal and neonatal Hb and Hct levels indicates that physiological changes during pregnancy may protect the newborn from disorders such as anemia, even when maternal Hb levels are low. The results suggest the importance of developing health policies and interventions that address the newborn and the mother separately, as maternal physiological changes during pregnancy appear to confer hematological protection to the newborn.